Alvin-Toffler on the Future - Geary, R.C. (Economic & Social Studies, 1972)
This important book has the supreme merit that it makes one think. One's conclusions may differ from the author's everion his own very voluminous data and may differ more on attaching weight to factors of which he is deemed to take insufficient account.
Keywords: Book Review